2011
DOI: 10.4097/kjae.2011.61.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative nausea and vomiting after mastoidectomy with tympanoplasty: a comparison between TIVA with propofol-remifentanil and balanced anesthesia with sevoflurane-remifentanil

Abstract: BackgroundThere is growing interest in the anesthetic approach using total intravenous anesthesia (TIVA) with propofol and remifentanil for the prevention of postoperative nausea and vomiting (PONV). The aim of this study was to compare between the two anesthetic techniques for preventing PONV in the patients undergoing mastoidectomy with tympanoplasty.MethodsAfter obtaining informed consent, 62 patients aged between 20 to 60 years undergoing elective mastoidectomy and tympanoplasty were randomized into two eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
1
16
0
5
Order By: Relevance
“…In our study without prophylactic atropine, nausea was found in 62.2% of the patients in the midazolam–ketamine group and vomiting was found in 33.6% of these patients, which is higher than the findings of previous studies. Propofol has been shown to have antiemetic effects in different surgical procedures 4043. In our study, significantly less nausea and vomiting was also observed in the fentanyl–propofol group.…”
Section: Discussionsupporting
confidence: 68%
“…In our study without prophylactic atropine, nausea was found in 62.2% of the patients in the midazolam–ketamine group and vomiting was found in 33.6% of these patients, which is higher than the findings of previous studies. Propofol has been shown to have antiemetic effects in different surgical procedures 4043. In our study, significantly less nausea and vomiting was also observed in the fentanyl–propofol group.…”
Section: Discussionsupporting
confidence: 68%
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine trials reported pain intensity at or around 24 h postsurgery, in which 595 patients received propofol anaesthesia, while 586 had inhalational anaesthesia [10,11,18,19,21,22,25,28,29]. Overall, compared with inhalational anaesthetics, patients who received propofol reported significantly lower pain scores 24 h postsurgery (Hedge's g (95% CI) À0.134 (À0.248 to À0.021) (p = 0.021) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our research, there was no significant difference in the percentage of postoperative nausea and vomiting between the two groups. This is believed to be attributed to the short operation and anesthesia time because the intubation time was shorter and a reduced amount of inhalation anesthesia was used [16,17]. …”
Section: Discussionmentioning
confidence: 99%